2023
DOI: 10.15561/26649837.2023.0306
|View full text |Cite
|
Sign up to set email alerts
|

Instructional cues in the teaching of dribbling in school physical education classes

Abstract: Background and Study Aim. A cue is a short and concise instruction about the key aspects of a successful performance. In addition to an attentional strategy, an instructional cue has been considered as a Physical Education teaching content for developing the students' knowledge about performing motor skills. This study investigated the effects of perceptual and motor instructional cues on the learning of dribbling during physical education classes at school. Material and Methods. The sample comprised 81 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The second was that by knowing which components are integral parts of a FMS, PE teachers, for example, could use these components to provide tips or instructions so that children may improve their performance. It has been shown that instructions or cues/tips during PE classes about the movement's quality can help improve FMS and sports skills (Ignico, 1991;Pontes et al, 2023). Further, it has also been shown how these instructions can be important for children to improve their performance and transfer their FMS advancement to more complex skills (dos Pacheco et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The second was that by knowing which components are integral parts of a FMS, PE teachers, for example, could use these components to provide tips or instructions so that children may improve their performance. It has been shown that instructions or cues/tips during PE classes about the movement's quality can help improve FMS and sports skills (Ignico, 1991;Pontes et al, 2023). Further, it has also been shown how these instructions can be important for children to improve their performance and transfer their FMS advancement to more complex skills (dos Pacheco et al, 2021).…”
Section: Discussionmentioning
confidence: 99%